Impact of Corporate Governance on Corporate Firm Value: A Case of Nepalese Commercial Banks - Budhathoki, Subas; Adhikari, Shovita (Nepalese Journal of Finance, 2024)
The study examines the impact of corporate governance on corporate firm value of Nepalese commercial banks. Earnings per share and market capitalization are selected as the dependent variables. The selected independent variables are board size, board gender diversity, audit committee, board independence, financial leverage, corporate size, and bank age. The study is based on secondary data of 15 commercial banks with 105 observations for the study period from 2014/15 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the corporate firm value of Nepalese commercial banks. The study showed that board independence has a negative impact on earnings per share and market capitalization. It indicates that presence of independent board of director leads to decrease in earnings per share and market capitalization. Similarly, corporate size has a positive impact on earnings per share. It indicates that increase in corporate size leads to increase in earnings per share. Similarly, bank age has a positive impact on earnings per share and market capitalization. It indicates that increase in bank age leads to increase in earnings per share and market capitalization. Further, the study also showed that board size has a positive impact on earnings per share. It indicates that increase in board size leads to increase in earnings per share. Similarly, financial leverage has a positive impact on market capitalization. It indicates that increase in financial leverage leads to increase in market capitalization. Likewise, board gender diversity has a negative impact on earnings per share. It indicates that presence of female board of director leads to decrease in earnings per share. In addition, audit committee has a positive impact on earnings per share. It implies that increase in audit committee member leads to increase in earnings per share.